Aerodynamic analysis of store jettison on a helicopter - Ryu, M.; Shin, P.; Lee, T.; Hwang, Y.; Lammers, K.; Bruin, A. de (My University, 2019)
Aerodynamic analysis of the store jettison on a helicopter was performed in this paper. The objective of the present study is to investigate the aerodynamic characteristics of a jettisoned store from a helicopter. Transient, incompressible, three-dimensional and turbulent flow in the store jettison with rotor downwash was analyzed using commercial computational fluid dynamics software. Virtual blade method was adopted to describe the effect of rotor down wash. Overset meshes were used to consider a movement of the jettisoned store. Computational results are validated by dynamically scaled free drop wind tunnel testing. The wind tunnel testing was executed at low-speed tunnel of the German-Dutch wind tunnel (DNW-LST). Calculated results are good agreement with wind tunnel testing results. The trajectories of the store are mainly affected by the weight of jettisoned store.